2020
DOI: 10.1136/tobaccocontrol-2019-055114
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of heated tobacco product use and its relationship with attempts to quit cigarette smoking among Korean adolescents

Abstract: IntroductionHeated tobacco products (HTPs) have been available in the Korean market since June 2017. In this study, we examined the prevalence and predictors of HTP use among Korean adolescents and the association between HTP and electronic cigarette (EC) use and attempts to quit conventional cigarette (CC) smoking.MethodsWe analysed the data of a representative sample (n=60 040) of 13–18-year-old middle-school and high-school students in Korea who had participated in the 14th Korea Youth Risk Behavior Web-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 23 publications
2
43
0
3
Order By: Relevance
“…The odds of HTP use were much greater in EC users than in CC users, as with prior studies 7,9,12 . Among CC-only users, moderate smokers were more likely to use HTPs as in a previous study 9 .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The odds of HTP use were much greater in EC users than in CC users, as with prior studies 7,9,12 . Among CC-only users, moderate smokers were more likely to use HTPs as in a previous study 9 .…”
Section: Discussionsupporting
confidence: 78%
“…significantly less likely to be former CC users despite having made more attempts at smoking cessation 12 .…”
mentioning
confidence: 98%
“…According to another Korean study using KYRBS 2019 data, ever HTP use among adolescents was greater among men, higher-grade students, current cigarette smokers and/or e-cigarette users, and risky alcohol drinkers. 39) In one Japanese study, the prevalence of HTP use among adult men was highest among the following groups: individuals aged 20-49 years old, with 10 or more years of education, who were not bereaved or divorced, with high household income, who were current internet users, and with risky behaviors related to alcohol. Among adult women, those who were 20-39 years old, with 15 or fewer years of education, with a household size of three or more people, employed or self-employed, current internet users, and with risky behaviors related to alcohol were more likely to use HTPs.…”
Section: Characteristics Of Heated Tobacco Product Usersmentioning
confidence: 99%
“…First, the prevalence of ever (former or current) and current HTP users among Korean adolescents was 4.9% and 2.6%, respectively, within two years of the launch of HTPs. Compared to the previous year (2.9%) [ 13 ], the prevalence of ever HTP users increased by approximately 1.8 times (2.0% p). Moreover, the 2019 prevalence of current HTP use among adolescents was slightly higher than among adults (2.1%) in 2018 from a study on Korean adults [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Korea revealed that 2.9% of Korean adolescents (men: 4.4%, women: 1.2%) were HTP ever users, most of whom were dual users of HTP and CC or triple users of HTP, CC, and electronic cigarettes (EC). However, due to the unavailability of data, it was not possible to assess current or former HTP use status and related factors in the aforementioned study [ 13 ]. Dual or poly-tobacco use among adolescents is a public health problem [ 14 ].…”
Section: Introductionmentioning
confidence: 99%